Psikoedukasi Peningkatan Kontrol Diri untuk Mengurangi Kecanduan Internet pada Siswa SMP: Psychoeducation to Improve Self-Control to Reduce Internet Addiction in Junior High School Students - Mutiara Shafiya Irawan; Zaki Nur Fahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Internet use among adolescents has increased significantly, raising concerns about internet addiction and its psychological consequences. Specific Background: Students at SMP Negeri 1 Jabon showed patterns of excessive internet use associated with low self-control, indicating the need for structured intervention within the school setting. Knowledge Gap: Although prior studies have established a relationship between self-control and internet addiction, empirical evidence examining school-based psychoeducation programs targeting self-control improvement remains limited in this specific context. Aims: This study aimed to evaluate whether psychoeducation focused on self-control was associated with changes in students’ internet addiction levels. Results: Using a pretest-posttest design, statistical analysis revealed significant differences between pre-intervention and post-intervention scores, indicating increased self-control and decreased internet addiction tendencies after program implementation. Novelty: The study provides contextual empirical findings from a structured psychoeducational intervention conducted directly within a junior high school environment using quantitative evaluation. Implications: These findings support the integration of preventive psychoeducation programs in schools to promote healthier digital behavior and strengthen adolescents’ regulatory capacity in managing internet use. Keywords: Self Control, Internet Addiction, Psychoeducation, Adolescents, Pretest Posttest Design Key Findings Highlights: Statistical comparison demonstrated significant score differences after intervention delivery. Program implementation within junior high school setting showed measurable behavioral change. Quantitative evaluation confirmed reduction in excessive online usage tendencies.